Evaluation of Anti-efflux Activity of Anthemis atropatana Extract against Ciprofloxacin Resistant Staphylococcus aureus Isolates - Sh Ezati; A Mirzaie; M Zandi (Institue of Medicinal Plants, ACECR, 2018)
Background: Antibiotic resistant Staphylococcus aureus isolates are the main nosocomial infection agent and the norB efflux pump plays an important role in antibiotic resistance. Objective: The aim of this study was to investigate the chemical composition of Anthemis atropatana extract and analysis of its anti-efflux activity on ciprofloxacin resistant Staphylococcus aureus strains. Methods: In this experimental study, the A. atropatana extract was prepared by maceration technique and its phytochemical composition was analyzed by GC/MS method. Subsequently, norB efflux pump was detected in 50 clinical isolates of S. aureus using cartwheel and PCR methods. Finally, after treatment of strains with SubMIC concentration of extract, its anti-efflux activity was evaluated via Real Time PCR. Results: GC-MS analysis of A. atropatana extract was shown the most frequent component was belonged to Dodecane (9.8%) and Tridecane (6.4%). Moreover, the cartwheel and PCR methods was showed that out of 50 isolates, 10 isolates had norB efflux pump. In addition to, after treatment of strains with subMIC concentration of A. atropatana extract, the Real Time PCR results was indicated that the norB gene expression was down-regulated. Conclusion: Based on the results obtained in this study, it seems that the extract has potential uses for pharmaceutical industries.